2007
DOI: 10.1080/00103620701663081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium/Magnesium Ratio in Soil on Magnesium Availability, Yield, and Yield Components of Maize

Abstract: The effect of calcium (Ca)/magnesium (Mg) ratio in the soil on Mg availability, yield, and yield components of maize (Zea mays L.) was investigated both in the greenhouse and the field at eight different Ca/Mg ratios ranging from 1:1 and 8:1. In the greenhouse, exchangeable Ca/Mg ratios of 2:1 to 3:1 gave optimum yield of maize without Mg-deficiency symptoms. The Ca/Mg ratios in the soil were positively and significantly correlated with Ca content and negatively and significantly correlated with Mg content. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Contrary to our findings where a Ca:Mg ratio below 2.3 had higher yield response, a study in seven agroecosystems from SSA by Kihara et al (2016) showed that clusters of non-responsiveness maize field trials had a Ca:Mg ratio of 2.6, on average, whereas the highly responsive cluster had a mean ratio of 4.5. A pot study of Osemwota et al (2007) with soils from southern Nigeria showed significantly greater uptake of Mg by maize for a soil with Ca:Mg ratio of 1 compared to 8; this result did not hold in field experiments and did not relate to differences in productivity. A pot experiment by Härdter et al (2004) illustrated a fourfold decrease in responses of maize production to NPK fertilizer when the Ca:Mg balance was raised from 1 to 10.…”
Section: Discussionmentioning
confidence: 91%
“…Contrary to our findings where a Ca:Mg ratio below 2.3 had higher yield response, a study in seven agroecosystems from SSA by Kihara et al (2016) showed that clusters of non-responsiveness maize field trials had a Ca:Mg ratio of 2.6, on average, whereas the highly responsive cluster had a mean ratio of 4.5. A pot study of Osemwota et al (2007) with soils from southern Nigeria showed significantly greater uptake of Mg by maize for a soil with Ca:Mg ratio of 1 compared to 8; this result did not hold in field experiments and did not relate to differences in productivity. A pot experiment by Härdter et al (2004) illustrated a fourfold decrease in responses of maize production to NPK fertilizer when the Ca:Mg balance was raised from 1 to 10.…”
Section: Discussionmentioning
confidence: 91%
“…The increase and the balance between Ca 2+ and Mg 2+ levels deeper in the soil after gypsum application are linked to the ion pairings with SO 4 2− (Michalovicz et al 2018), along with the complexation with organic acids from the decomposition of crop residues (Franchini et al 2003). The application of 12 Mg ha −1 , especially when combined to 2S and 3S splitting, resulted in Ca/Mg ratios that surpassed the optimum in the upper soil layers (0-0.4 m depth), which is 6:1 for corn yield (Osemwota et al 2007), and these results are in agreement with other studies (Caires et al 2004;Michalovicz et al 2018).…”
Section: Soil Chemical Attributesmentioning
confidence: 99%
“…Moreover, Mg and Ca appear to have an antagonistic relationship. Excessive Ca in soil leads to Mg deficiency, which may result in nutrient imbalances, depress Mg uptake by crop root, and in turn its translocation to plant parts and finally affect yields of crop . Gransee and Führs Reported that the soils with high pH favor Mg fertilizer solubility and the nutrient become available in the early stages of crop development.…”
Section: Discussionmentioning
confidence: 99%
“…44 Excessive Ca in soil leads to Mg deficiency, which may result in nutrient imbalances, depress Mg uptake by crop root, and in turn its translocation to plant parts and finally affect yields of crop. 45,46 Gransee and Führs 47 Reported that the soils with high pH favor Mg fertilizer solubility and the nutrient become available in the early stages of crop development. However, with the absorption of plants and the fixation of soil, the exchangeable Mg decreased gradually.…”
Section: Effects Of Mg Application On Total Mg Accumulation Amounts Imentioning
confidence: 99%